Pembelajaran Pendidikan Agama Katolik Berbasis Multimedia Pebelajaran Interaktif untuk Meningkatkan Minat Belajar Peserta Didik di SMA Negeri 1 Solor Selatan - Hergeka Hayon, Hendrika; Yosep Belen Keban; Benedikta Y. Kebingin (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
The purpose of this research was to determine Catholic religious education learning based on interactive learning multimedia to increase students’ interest in learning. Qualitative research with a descriptive approach was used in the study. This research was conducted at SMA Negeri 1 Solor Selatan, south with the implementation time starting from February to May 2025. The research subjects were 11 people, namely: 1 Catholic religious education teacher, 1 curriculum head, and 9 grade XI students. Data collection techniques used observation, interviews, and documentation. Data analysis teahniques used data reduction, data presentation, and drawing conclusions. The validity of the data in this study used data collection techniques and source triangulation. The results of this study indicate that the use of interactive learning multimedia can improve students’ understanding of moral and spiritual values. The response from stundents to the learning media used was very good, reflecting involvement in the learning process that can increase students’ interest in learning. The conclusion in this study is that interactive learning multimedia is supported as an effective learning tool to increase students’ interest in learning.